Obituary: The Passing Of Professor Mario Rutten (1958–2015) - Scrase, Tim (Penerbit Universiti Sains Malaysia (USM Press), 2016)
It is with great sadness for friends and colleagues in Asian Studies, and readers of the International Journal of Asia Pacific Studies (where Mario was an editorial board member), to hear of the recent passing of University of Amsterdam Professor Mario Rutten. Mario was born in Maastricht on 31 October 1958. After spending his childhood and youth with his siblings in various towns and cities of the Netherlands due to his father's employment, in 1984 he completed his MA degree in Sociology from Erasmus University Rotterdam, specialising in Organisation Sociology, Management and Comparative/Non-Western Sociology. He then moved to the University of Amsterdam where, under the guidance of renowned Asia scholar Professor Jan Breman, Mario completed his PhD degree in 1991 (with distinction) in the Social Sciences (Anthropology/Sociology) with a dissertation on "Capitalist Entrepreneurs and Economic Diversification: Social Profile of Large Farmers and Rural Industrialists in Central Gujarat, India." His doctoral studies were funded by the Foundation for the Advancement of Tropical Research (WOTRO) of the Netherlands Organization for Scientific Research (NWO) and during his field studies in India he became an affiliated researcher at the Centre for Social Studies, Surat.